SOCIAL RESPONSIBILITY OF INCLUSIVE EDUCATION OF HIGHER EDUCATION INSTITUTIONS IN CONDITIONS OF MILITARY CONFLICT - Батченко, Людмила В.; Штулер, Ірина Ю.; Баула, Олексій В. (Journal of Strategic Economic Research, 2024)
Inclusive education is a key element of the modern educational system, aimed at ensuring equal opportunities and access to quality education for all students, regardless of their specific needs. In the context of military conflict, the challenges faced by higher education institutions become particularly acute and require urgent and effective solutions. This research is focused on analyzing the current state of inclusive education in the conditions of military conflict, evaluating the social responsibility of universities in such circumstances, and identifying prospects and directions for further research in this important field. The hypothesis of the study is that the integration of effective inclusive education strategies, adapted to the conditions of military conflict, can significantly improve the quality of education and ensure equal access to learning for all students, including those with special educational needs. The purpose of the study is to analyze the impact of military conflict on inclusive education in higher education institutions, identify strategies to enhance its effectiveness and social responsibility, and explore prospects and directions for further research in this field. The research methods included the analysis of scientific literature related to inclusive education and its challenges in the context of military conflict, conducting surveys among education professionals, and analyzing statistical data on the impact of military conflicts on the educational process. Additionally, case study methods were used to examine specific examples of inclusive education in conflict conditions. The results of the study showed that military conflict significantly complicates the provision of inclusive education in higher education institutions. The need to adapt educational programs and methods to conflict conditions was identified, particularly through the implementation of flexible curricula and the use of distance learning technologies. The importance of the social responsibility of universities in ensuring access to education for all students, including those with special educational needs, is also emphasized. The conclusions of the study indicate significant challenges that arise for inclusive education in the context of military conflict. However, there are effective strategies for adaptation and innovation capable of ensuring accessibility and quality of education for all students. The social responsibility of universities is crucial, as well as the need to integrate flexible educational approaches and distance learning technologies. The research also highlights the need for further studies in this field, particularly in the context of developing effective policies and support programs for inclusive education.